Improving integrated wildfire management in the Fynbos Biome of South Africa using information on synoptic-scale atmospheric features that promote wildfires - Harrison, Dean Charles (Department of Environmental and Geographical Science, 2016)
Wildfire, an essential element for the Fynbos Biome of South Africa, can be a threat to property and human life if it is not well managed. Despite many studies on the dynamics and management of wildfire, the role of the atmosphere in inducing regional circulations that promote widespread wildfire is not well known. This dissertation studies the characteristics of wildfire in the Fynbos Biome, identifies synoptic-scale atmospheric features that produce favourable conditions for the wildfire, and examines possibility of using the features as indicators for wildfire occurrence. Ten years (2003 - 2012) of fire data from the MODIS "active-fires" datasets were analysed over the study domain. Daily Fire Danger Index (FDI) was calculated over Southern Africa for this period using maximum temperature (Tmax), minimum relative humidity (RHmin), and maximum wind speed (Wmax) data from the Climate Forecasting System Reanalysis datasets (CFSR) at a 0.5°x0.5° horizontal resolution. The Self Organising Maps (SOMs) technique was used to classify the FDI (anomaly) patterns on the fire days, and the atmospheric dynamics associated with each pattern were studied.